Targeting phosphorylated p53 to elicit tumor-reactive T helper responses against head and neck squamous cell carcinoma. (2nd September 2018) - Ohara, Kenzo; Ohkuri, Takayuki; Kumai, Takumi; Nagato, Toshihiro; Nozaki, Yui; Ishibashi, Kei; Kosaka, Akemi; Nagata, Marino; Harabuchi, Shohei; Ohara, Mizuho; Oikawa, Kensuke; Aoki, Naoko; et al.
ABSTRACT: The human T cell receptor is capable of distinguishing between normal and post-translationally modified peptides. Because aberrant phosphorylation of cellular proteins is a hallmark of malignant transformation, the expression of the phosphorylated epitope could be an ideal antigen to combat cancer without damaging normal tissues. p53 activates transcription factors to suppress tumors by upregulating growth arrest and apoptosis-related genes. In response to DNA damage, p53 is phosphorylated at multiple sites including Ser33 and Ser37. Here, we identified phosphorylated peptide epitopes from p53 that could elicit effective T helper responses. These epitope peptides, p5322-41/Phospho-S33 and p5322-41/Phospho-S37, induced T helper responses against tumor cells expressing the phosphorylated p53 protein. Moreover, chemotherapeutic agents augmented the responses of such CD4 T cells via upregulation of phosphorylated p53. The upregulation of phosphorylated p53 expression by chemotherapy was confirmed in in vitro and xenograft models. We evaluated phosphorylated p53 expression in the clinical samples of oropharyngeal squamous cell carcinoma and revealed that 13/24 cases (54%) were positive for phosphorylated p53. Importantly, the lymphocytes specific for the phosphorylated p53 peptide epitopes were observed in the head and neck squamous cell cancer (HNSCC) patients. These results reveal that a combination of phosphorylated p53 peptides and chemotherapy could be a novel immunologic approach to treat HNSCC patients.